Enhancing surface properties of Ti via pulsed laser ablation in H2O2: Formation of stable TiO2-B structure with improved corrosion and wear resistance - Ensiye Shabanlou; Babak Jaleh; Maryam Molaei; Mohammad Kashfi; Saeid Azizian; Arash Fattah-Alhosseini; Kyong Yop Rhee (Journal of Materials Research and Technology)
Recently, laser surface modification has emerged as a promising approach to improve the mechanical features of titanium (Ti), such as corrosion and wear resistance, as well as hardness. In this study, a simple, environmentally friendly, controllable, and cost-effective pulsed laser ablation (PLA) method was applied to form the titanium dioxide (TiO2) ceramic structure on the surface of Ti metal. For the first time, hydrogen peroxide (H2O2) was used as an irradiation environment to modify the surface properties of Ti. The effects of different numbers of laser scanning cycles on the generated TiO2 structures and their corrosion behaviors were studied. The ablated samples were characterized using X-ray diffraction (XRD), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The results confirmed the fabrication of the monoclinic TiO2-B structure (bronze phase of TiO2) for all numbers of laser scanning cycles. The TiO2-B structure formed on the Ti surface after PLA positively affected its wear and corrosion resistances in Ringer's solution. Therefore, laser ablation of Ti in H2O2 aqueous solution is a facile approach to form stable TiO2-B and it improves the wear and corrosion resistances of Ti.